Deformasi Ayam Bangkok Sebagai Ide Penciptaan Karya Kayu - Rendy Syah Putra; Wisnu Prastawa (Penerbit dan Percetakan, CV. Picmotiv, 2025)
This work raises the Deformation of Bangkok Chicken as an Idea for Creating Wood Works. The specialty of Bangkok chicken has the potential to be used as an idea for creating wood works, the meaning and philosophy of Bangkok chicken as the basis for the concept that will be realized in the creation. The process of creating this work is carried out through three main stages, namely exploration, design, and embodiment. The exploration stage is carried out by directly observing the characteristics of Bangkok chicken as the main object in making this work, then at the design stage the ideas and concepts that have been obtained are poured into several alternative sketches. From the sketches that have been made, they will then be selected to be used as designs that will be realized into works of art. Furthermore, the embodiment stage will start from the selected design and use surian wood as the main medium, the technique that will be used is medium relief carving (mezzo relief). While the finishing process will be carried out by applying print ink which will then be coated using clear doft, this coating aims to protect the color of the work so that it remains durable and long lasting. The works that will be produced are seven pieces and have the main function as room decorations.